Tatak Noy-Pi the branding evolution of Tesoro's Philippine Handicrafts - a Philippine creative and cultural industry - Villanueva, Regine Remolano 1994-; Villanueva, Regine Remolano; Pernia, Elena E.; University of the Philippines Diliman. College of Mass Communication (Quezon City University of the Philippines Diliman, 2015)
"The study looks into how a cultural industry such as Tesoro's Philippine Handicrafts underwent the brand revitalization process throughout its 70 years of existence in the Philippine market. This study uses a historical approach which analyzes the changes in product development and promotional strategies. Similarly, its brand identity was determined as well in terms of its internal process and archival data such as history, mission-vision, customer relations, products, and promotions. The product life cycle model and the brand identity planning model were used as theoretical framework for the study. The life cycle was used in historically tracing the company's developments and changes in terms of its branding, more specifically the products, promotions and identity. Interviews were conducted among informants who included the CEO and the heads of each department in the business. The searcher also utilizes textual analysis to have an in-depth understanding of Tesoro's' brand identity portrayal through its advertisements. The results showed how the company has undergone a progressive and innovative transition in its cycle. With the changing markets and increased competition, the brand started active promotions and engaged in product development. In terms of identity, they are branded as pioneers of the handicraft industry in the Philippines. They started their brand revitalization to be able to imbibe this identity to their consumers through advertisement communication and identifying their segment markets."
Vita.
Undergraduate thesis
Keywords: Business names -- Philippines; Branding (Marketing) -- Philippines; Creative ability in business